2018
DOI: 10.1111/cid.12660
|View full text |Cite
|
Sign up to set email alerts
|

Does intraoperative perforation of Schneiderian membrane during sinus lift surgery causes an increased the risk of implants failure?: A systematic review and meta regression analysis

Abstract: The results of this study showed that an intraoperative SM perforation could increase the risk of implant failure after the sinus lift surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 56 publications
3
41
1
6
Order By: Relevance
“…Perforation of the sinus membrane did not seem to be associated with implant failure in this study. A recent systematic review on 58 included studies reported that an intraoperative sinus membrane perforation could increase the risk of implant failure after sinus augmentation surgery (27). The authors commented that this positive relationship could be explained by the event of displacement of bone particles through the perforation, even in the event of membrane repair, resulting in chronic infection, bone graft resorption and reduction in bone formation (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perforation of the sinus membrane did not seem to be associated with implant failure in this study. A recent systematic review on 58 included studies reported that an intraoperative sinus membrane perforation could increase the risk of implant failure after sinus augmentation surgery (27). The authors commented that this positive relationship could be explained by the event of displacement of bone particles through the perforation, even in the event of membrane repair, resulting in chronic infection, bone graft resorption and reduction in bone formation (27).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review on 58 included studies reported that an intraoperative sinus membrane perforation could increase the risk of implant failure after sinus augmentation surgery (27). The authors commented that this positive relationship could be explained by the event of displacement of bone particles through the perforation, even in the event of membrane repair, resulting in chronic infection, bone graft resorption and reduction in bone formation (27). We cannot truly assess whether the use of PRGF as a membrane to repair sinus membrane perforation or mixed with the bone grafting material may have reduced complications associated with perforations in our study.…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant gain in antral bone in the group that received bone grafting (P = 0.02). Essam Al-Moraissi [34], reported in a systematic review of the literature that there is a statistically significant correlation between Schneiderian membrane perforations and implant failure rate. In the present study, patients included in the analysis presented at the base-line with a residual bone height ranging from 4.10 to 6.90 mm (mean 5.89 ± 0.68 mm), demonstrated with linear measurements on CBCT.…”
Section: Discussionmentioning
confidence: 99%
“…Una de las complicaciones más frecuentes es la perforación de la membrana de Schneider con una prevalencia de 7%-44% (17). Diferentes factores podrían contribuir a una perforación de membrana como el uso de instrumentos rotatorios, hueso residual en altura deficiente, pacientes fumadores y cambios en el espesor de la membrana (18).…”
Section: Perforación De Membranaunclassified
“…Hubo una correlación positiva estadísticamente significativa entre la tasa de implantes fallidos y el número de perforaciones de la membrana sinusal. La tasa de fracaso de implantes fue de 10.3%, cuando los implantes fueron colocados en esos sitios, mientras que la tasa de implantes perdidos fue de 2.4% en sitios no perforados (17). Se refiere que, como consecuencia de estas perforaciones, grandes o pequeñas, habría la posibilidad de que estos materiales de injerto puedan iniciar una inflamación local, ocasionando incluso una sinusitis crónica, perdiendo parte o todo el material de injerto, pudiendo ocasionar la pérdida del implante incluso antes de ser sometido a fuerzas oclusales.…”
Section: Perforación De Membranaunclassified